2011
DOI: 10.1111/j.1651-2227.2011.02277.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin‐converting enzyme gene polymorphism in persistent pulmonary hypertension of the newborn

Abstract: Angiotensin-converting enzyme gene polymorphism did not impact the risk or severity of PPHN among infants ≥ 34 weeks GA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Moreover, the 6A3 allele of surfactant protein A1(SP-A1) was less common among preterm infants with RDS and was absent among those with severe RDS, which suggests a possible protective role for this allele or other genes with which it is in linkage disequilibrium in RDS [11]. Glutathione-S-transferase-P1 (GSTP1) I105V polymorphism and Angiotensin converting enzyme (ACE) gene deletion/deletion polymorphism have also been reported to be protective factors for respiratory distress in preterm infants, and another study showed that angiotensin-converting enzyme gene polymorphism did not impact the risk or severity of persistent pulmonary hypertension of the newborn among infants >34 weeks GA [16-18]. Many of these associations with RDS have not been tested in multiple independent populations or have not been consistently replicated across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the 6A3 allele of surfactant protein A1(SP-A1) was less common among preterm infants with RDS and was absent among those with severe RDS, which suggests a possible protective role for this allele or other genes with which it is in linkage disequilibrium in RDS [11]. Glutathione-S-transferase-P1 (GSTP1) I105V polymorphism and Angiotensin converting enzyme (ACE) gene deletion/deletion polymorphism have also been reported to be protective factors for respiratory distress in preterm infants, and another study showed that angiotensin-converting enzyme gene polymorphism did not impact the risk or severity of persistent pulmonary hypertension of the newborn among infants >34 weeks GA [16-18]. Many of these associations with RDS have not been tested in multiple independent populations or have not been consistently replicated across studies.…”
Section: Discussionmentioning
confidence: 99%
“…ACE is predominantly expressed in the pulmonary microvascular endothelial cells, which is in contrast to that of other organs where ACE is expressed in the arteries . The most AT‐II conversion via ACE within the body occurs during pulmonary blood perfusion . Because of the angiogenic function of AT‐II, ACE has been suggested to play a role in vascular remodeling, pulmonary hypertension and in the pathomechanism of neonatal lung diseases .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The most AT-II conversion via ACE within the body occurs during pulmonary blood perfusion. 9 Because of the angiogenic function of AT-II, ACE has been suggested to play a role in vascular remodeling, pulmonary hypertension 10 and in the pathomechanism of neonatal lung diseases. [11][12][13][14] ACE inhibitor ingestion during pregnancy has been linked to human pulmonary hypoplasia as part of a general ACE-induced fetopathy.…”
Section: Introductionmentioning
confidence: 99%